New approach for evaluation of the performance of spectral amplitude coding-optical code division multiple access system on high-speed data rate - Thanaa Hussein, Abd.; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil, Dr.; R. Badlishah, Ahmad, Prof. Dr.; Mohd Abdur, Rashid, Dr. (The Institution of Engineering and Technology, 2013)
Link to publisher's homepage at www.ietdl.org